Inspiration and fixation: Questions, methods, findings, and challenges - Vasconcelos, Luis A.; Crilly, Nathan (Design studies, 2016)
Research into inspiration and fixation has produced a complex web of questions, methods, and findings, making it difficult to know what has already been investigated and learnt, and what to investigate next and how. To address this, we review the literature, focussing on 25 studies that adopt a similar experimental approach. This reveals 14 manipulated variables, relating to properties of the inspiration source and features of the design process. However, whilst these studies follow a similar approach, when scrutinised and compared, they show great variety in the methods used and the results obtained. We discuss this diversity, offering a methodological critique of inspiration and fixation research and providing recommendations for how future studies might be conducted and reported. •We performed a methodological review of studies into inspiration and fixation.•We found 14 variables that have been systematically manipulated in the studies.•We also found variables often not observed and great variation in the evaluation.•We discuss different perspectives to explain design fixation and similar effects.•We suggest formalisation and inclusion of methods, and propose research questions.